STUDENTS’ EXPERIENCES IN ENGLISH FOR E-TOURISM: A CASE STUDY OF CHALLENGES AND PERCEPTIONS - Suharto, Ririn Pratiwi (NextGen Education Review Journal, 2024)
English for E-Tourism is a course in English for Tourism Industry. The goal of this course is designed to meet the needs of the tourism industry. This course is designed to produce electronic tourism products by using English. The problem faced is that students have lack of knowledge regarding to English for E-Tourism. The aim of this research is to identify students’ experiences in producing electronic tourism products as learning output in English for E-Tourism course. Data was taken from interviews and questionnaires. It is a case study in which is identifying student challenges and perception on English for E-Tourism. The research results show that students are able to think creatively to produce electronic tourism products, such as online tourism guidebooks and promotional videos. The research results were used as a learning model for English for E-Tourism in the future.